(3CecfI GdYQH hejGggGs - (3GdCUHgGfj, CHh Ydj, dZOI Ch dZPI Ch dcPI, dZOI, GdMSf Hf eMeO GdCUagGfj, J fMh (B311(3g` (B923(3es ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3ChdgG(B: (3bGd CHh Ydj dZOI GdCUHgGfj(B: (3bGd CHh GdhQO GdYbjdj(B: (3ef ejGg Hfj Ybjd HfLO(B: (3GdbdH, hgj dHfj YGeQ dG jTQcge ajgG CMOs
(3BNQgG (B:s
(3BNQgG(B: (3hGdQJbGA CjVG gVHI dHfj cdGH cGfJ cYGHI dHfj LYaQ Hf EHQGgje hgj Gdjhe dHfj CHj eQje hgj Hjf GdUaQGA hHjf GdCKjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 212s
(3GdCYdGe, L (B2: 212s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMZQGajG hGdHdOGfs